Analysis of Longitudinal Electroexcitation for Positive and Negative Parity States of 36,40Ar Nuclei Using Different Model Spaces - Abdulhasan, A. A.; Dakhil, Z. A. (Iraqi Journal of Science, 2023)
The nuclear structure for the positive ( ) States and negative ( ) states of 36,40Ar nuclei have been studied via electromagnetic transitions within the framework of shell model. The shell model analysis has been performed for the electromagnetic properties, in particular, the excitation energies, occupancies numbers, the transition strengths B(CL) and the elastic and inelastic electron scattering longitudinal form factors. Different model spaces with different appropriate interactions have been considered for all selected states. The deduced results for the (CL) longitudinal form factors and other properties have been discussed and compared with the available experimental data. The inclusion of the effective charges are essential for obtaining a reasonable description for the data. The results of sdpf-model space with sdpfk and sdpfmu-interactions have a good improved for the ground state form factors for 36,40Ar and for excitation properties of and state of 36Ar nucleus.